El juego teatral como estrategia para mejorar la postura corporal de los estudiantes de grado quinto del Colegio Colombo Florida Bilingüe (2019)
This research work was carried out at the Antonio Nariño University during the pedagogical practices, which are taken in the last three semesters of the basic education degree with emphasis on artistic and cultural education, therefore a follow-up was carried out and proposals were developed. of pedagogical approaches from theatrical practice, such as theatrical games, to improve the body image of fifth grade students at the Colombo Florida Bilingual School for students between 10 and 12 years of age, the follow-up is focused on body postures since it was evident that they tend to present inadequate postures in the educational field, from poor alignment of the spine, the position of the shoulders as well as the position of the head, this is obtained because the students They still do not recognize what the appropriate body postures are.